Mindfulness Technique and Lavender Aromatherapy on Anxiety in Cervical Cancer Patients Undergoing Chemotherapy - Rosniati Rosniati; Erika Erika; Nurul Huda; Sri Wahyuni; Misrawati Misrawati (Indonesian Journal of Global Health Research, 2025)
Mindfulness technique and lavender aromatherapy in reducing anxiety levels in cervical cancer patients undergoing chemotherapy. This research method uses a quasi-experimental design with a one-group pretest-posttest approach. A total of 49 respondents who experienced mild to moderate anxiety were involved in this study. The level of patient anxiety was measured before and after the intervention using the Hamilton Anxiety Rating Scale (HARS) questionnaire. The interventions provided included mindfulness technique training and lavender aromatherapy during chemotherapy sessions. The results showed a significant decrease in patient anxiety levels after the intervention, with the average anxiety level dropping from 43.40 to 34.26. The results of the paired sample t-test statistical test showed a p value <0.05, indicating that mindfulness and lavender aromatherapy interventions were effective in reducing anxiety in cervical cancer patients undergoing chemotherapy. Based on these findings, mindfulness and lavender aromatherapy interventions can be integrated as complementary therapies in cancer patient care to reduce anxiety during the treatment process. This study supports Calista Roy's adaptation theory, which emphasizes the importance of environmental interventions in helping patients adapt emotionally and physically to the disease. Suggestions for educational and health institutions are to integrate mindfulness techniques and lavender aromatherapy into nursing curricula and clinical practice to improve the well-being of cancer patients. These techniques can also be applied independently by the community as a simple way to manage everyday anxiety.